Vibration analysis of composite exhaust manifold for diesel engine using CFD. (April 2022) - Kumar, R. Ramesh; Razak, Abdul; Alshahrani, Saad; Sharma, Abhishek; Thakur, Deepak; Shaik, Saboor; Saleel, C Ahamed; Afzal, Asif
Abstract: Researchers used computer-aided design and computational fluid dynamics methodologies to establish the flow simulation process and find the critical level temperatures. CATIA V5 R20 has been used to create the geometric model. As a result, the normal study state conditions are performed at varied coefficient levels in all boundary areas. Three solid dimensioning approaches were used in the simulation process. The internal flow structures and velocity contours were obtained using computational fluid dynamics flow software. As a result, the structural elements in the exhaust manifold were mapped from a minimum range of 0.2933 to a maximum range of 0.99995 under various thermal conditions. The gradient temperature and velocity contour findings were absorbed in a flow process with maximum energy transmit of 0.2917 m/s and a temperature of 350 °C calculated using Computational fluid dynamics (CFD) techniques. The simulated data found the failure areas at the bottom of the exhaust manifold. At 0.005% of the input conditions, the stress concentrations were detected. Computational fluid dynamics simulation techniques reduced stress concentration levels by 14%.